PENGARUH PERSEPSI NEGARA ASAL TERHADAP MINAT MEMBELI DI MEDIASI BRAND IMAGE PADA BISNIS FASHION DI UNIVERSITAS CIPUTRA - Weldy Erlianto; Deandra Vidyanata (Universitas Ciputra Surabaya, 2021)
This research is done to see the effect that is formed in the relationship of Country of Origin variable on purchase intention that is mediated by brand image on start-up business entrepreneurs at Universitas Ciputra. Country of Origin is theoretical basis in this research because it is evaluated important to be consideration by related entrepreneur to increase purchase intention and brand image. This research uses purposive sampling in sampling process, and is obtained as many as 100 respondents with various kinds of business that are registered at Universitas Ciputra. The findings of this research result prove that start-up business needs (COO) variable to increase purchase intention, because through the research result of (COO) variable is able to increase purchase intention positively and significantly, then the result that is given (COO) on brand image variable is also obtained positive and significant results, and the last relationship between brand image variable on purchase intention also obtains positive and significant results.